Sistem Pengisian Pulsa Pada KWH Meter Prabayar Menggunakan Ponsel - Asep Mulyana; Tengku Ahmad Riza; Dadan Nur Ramadan; Muhammad Dzakwan Falih (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
There are two ways of billing system currently applied by PT PLN to bill electric power usage by subscriber, ie : conventional system and token system. In the conventional system done by staff by attending the location of the subscriber’s KWH Meter for recording the position of KWH Meter as data tobe used for billing system. The disadvantage of this way is the wasting time and costly. While the disadvantage of the token system is: no early warning when the token balance near to zero, but the power goes off suddenly. Another disadvantage of token system is the updating of balance of KWH Meter only can be done at one place, ie on the keypad near the KWH Meter device. It contrary with the updating way of the balance in mobile phone billing system thatr can be done "any place", by mean smart phone. In this research, designed a digital KWH Meter using Arduino Uno which equipped with communication system to get some features based on SMS as needed to solve those problems. The features are: the updating way of balance of KWH meter is integrated with mobile billing system, ie done by typing on the subscriber’s smart phone easily. Another feature is the checking of the remaining of the balance of KWH Meter also can be done on subscriber’s smart phone any where, any time. And the third feature is the early warning system (notifification message) to subscriber’s hand phone when the remaining of the balance of KWH meter reach the critical value according to preset value determined by subscriber to avoid the power source in the home goes off suddenly. As the final step of this research is the testing of the system which shown that the accuracy of KWH Meter by 99.34%, the average delay response of updating of the balance of KWH Meter (round trip delay) is 12,25 seconds, the delay response of balance checking of KWH Meter (round trip delay) is 14,25 seconds, and the delay of the early warning system (one way delay) is 7,15 seconds